2018
DOI: 10.3389/fpsyg.2018.01065
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Generalizability Theory Approach to College Students' Evaluation of Teaching

Abstract: Teachers' teaching level evaluation is an important component in classroom teaching and professional promotion in the institutions of higher learning in China. Many self-made questionnaires are currently being administered to Chinese college students to evaluate teachers' classroom teaching performance. Quite often, due to the absence of strong educational, and psychological measurements and theoretical foundations for these questionnaires, their dependability remains open to doubt. Evaluation time points, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The concept of teaching effectiveness is multifaceted and includes how instructors organise course content and communicate to learners (Staufenbiel, Seppelfricke and Rickers 2016). In a few instances, however, evidence from statistical procedures has come up against the multidimensional nature of teaching effectiveness (Li et al 2018); this happens when the scale fails the discriminant validity test. It is worth noting that whichever way is appropriate, only if adequate evidence exists for the decision made.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The concept of teaching effectiveness is multifaceted and includes how instructors organise course content and communicate to learners (Staufenbiel, Seppelfricke and Rickers 2016). In a few instances, however, evidence from statistical procedures has come up against the multidimensional nature of teaching effectiveness (Li et al 2018); this happens when the scale fails the discriminant validity test. It is worth noting that whichever way is appropriate, only if adequate evidence exists for the decision made.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some studies found out low validity of students' evaluation data (e.g. Feistauer and Richter 2016; Goos and Salomons 2016;Li et al 2018), others reveal that students' evaluation data can be highly valid (see VanLeeuwen, Dormody and Seevers 1999; Samian and Noor 2012; Ogbonnaya 2019). One major reason accounting for the mixed results centres on the approach used by these investigators.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations